Similar Gastro-Intestinal Exposure to Florfenicol After Oral or Intramuscular Administration in Pigs, Leading to Resistance Selection in Commensal Escherichia coli - De Smet, Joren; Boyen, Filip; Croubels, Siska; Rasschaert, Geertrui; Haesebrouck, Freddy; De Backer, Patrick; Devreese, Mathias (Frontiers in Pharmacology, 2018)
Florfenicol, which is licensed for veterinary use only, proves to be a potent antimicrobial for treatment of respiratory disease. However, the subsequent exposure of the gut microbiota to florfenicol is not well described. Hence, the effect of various administration protocols on both plasma and gastro-intestinal florfenicol concentrations in pigs was evaluated. In field situations were simulated by application of different administration routes and dosages (single oral bolus at 10 or 5 mg/kg body weight (BW), medicated feed at 10 or 5 mg/kg BW and intramuscular injections at 15 or 30 mg/kg BW). After intramuscular administration of 30 mg florfenicol/kg BW, gastro-intestinal concentrations of florfenicol, quantified 10 h after the last administration, were significantly elevated in comparison with the other treatment groups and ranging between 31.5 - 285.8 µg/g over the different gut segments. For the other treatment groups, the influence of dose and administration route was not significantly different. Bacteriological analysis of the faecal samples from the animals at the start of the experiment, demonstrated the presence of both florfenicol susceptible (with minimal inhibitory concentration (MIC) values of 2-16 µg/mL) and florfenicol resistant (MIC ≥256 µg/mL) Escherichia coli isolates in all treatment groups. Following, at 10 h after the last administration the susceptible Escherichia coli population was eradicated in all treatment groups due to the high intestinal florfenicol concentrations measured. Moreover, selection of the resistant Escherichia coli strains during treatment occurred in all groups. This is likely related to the fact that the different treatment strategies led to high gastro-intestinal concentrations albeit not reaching the high magnitude of MIC values associated with florfenicol resistance (≥256 µg/mL). Conclusively, in our experimental setup the administration route and dose alterations studied, had no influence on monitored florfenicol resistance selection in Escherichia coli from the microbiota.